INCOME DISTRIBUTION OF FARM SHARER BLIGON GOAT IN GOMBANG, PONJONG, GUNUNGKIDUL REGENCY - Kawuriaji, Nimas Resmita (Universitas Gadjah Mada, 2006)
This research was conductedto analyze the indome distribution of farm sharer Bligon goats in Gombang village, Ponjong district, GUnungkidul regency. The respondents in this study were all farmers who got Bligon goats first period sharing, totally 30 Farmer's. Farmer's data taken were input and output. Respondents who were taken with purposive sampling method were all farmers who got Bligon goat program on the first period. Measurement of farm's prosperity levels were done with Gini coefficient, Variation coefficient, and criteria of World Bank. Gini coefficient without goat sharing was 0.47; actual condition was 0.43; and after goat sharing receive assumption was 0.43. Coefficient of Variation without goat sharing was 98.53 percent; and actual condition was 88,71 percent; after got goat sharing was highly unbalanced, and after receiving goat sharing, income distribution got equally better. Result of this research indicated that Bligon goats increased farmer's income, as well as income distribution.